Black Carbon Emission and Wet Scavenging From Surface to the Top of Boundary Layer Over Beijing Region. Issue 17 (24th August 2020) - Liu, Dantong; Ding, Shuo; Zhao, Delong; Hu, Kang; Yu, Chenjie; Hu, Dawei; Wu, Yunfei; Zhou, Chang; Tian, Ping; Liu, Quan; Wu, Yangzhou; Zhang, Jiale; et al.
Abstract: The heating impacts caused by black carbon (BC) may modify the atmospheric dynamics of planetary boundary layer (PBL), essentially determined by its vertical distribution. In this study we performed simultaneous measurements of detailed BC properties at both surface (50 m) and mountain sites (1, 344 m) over Beijing region. The latter represents the top of PBL and was influenced by surface anthropogenic emissions, particularly around midday when PBL was developed, allowing continuous investigations on the evolution of BC during vertical transport in the PBL. Experiments in cold and warm seasons were performed to reflect seasonal difference in emission and meteorology: Winter had additional emission of residential heating and dry air; summer had moist air with more precipitation. The net ratio of BC/CO relative to background (ΔBC/ΔCO) is used to indicate the emission signature and scavenging of BC. At surface, both seasons peaked at similar ΔBC/ΔCO, however showed contrast shifts between both sites. In winter, mountain showed slightly higher ΔBC/ΔCO than surface due to receiving sources from wider area, whereas in summer, a refractory black carbon (rBC) mass scavenging efficiency of 35–62% was derived from the significantly lowered ΔBC/ΔCO on mountain. This scavenging process could incorporate BC into the summer moist air or low‐level clouds on a daily basis, exerting potential indirect effects. The resultant BC after scavenging exhibited smaller core size and increased coatings, leading to higher absorption efficiency by 45%. These factors should improve the representation of boundary layer processing of BC in evaluating its direct and indirect radiative impacts over the anthropogenically influenced region. Key Points: Measurements between surface and mountain sites were conducted simultaneously to investigate the evolution of BC during vertical transport Efficient upwards transport of BC to the top of boundary layer was observed in winter but subject to scavenging in summer BC after scavenging had smaller core size and enhanced coating in summer, leading to 45% absorption enhancement at mountain